Design, Synthesis, and Fungicidal Activities of Indole‐Modified Cinnamamide Derivatives. Issue 1 (8th December 2022) - Zhang, Xinwei; Fang, Jun; Li, Chenjie; Zhang, Jie; Yang, Shuwen; Deng, Bin; Tu, Song
Abstract: Dimethomorph is a kind of cinnamamide fungicide with high fungicidal activities for oomycete diseases. The commercially available dimethomorph is a mixture of two isomers, in which ( Z )‐dimethomorph possessing higher activity and ( E )‐dimethomorph possessing lower activity. Herein, we reported the design, synthesis and fungicidal activities of a series of novel indole‐modified cinnamamide derivatives, which used the indole group to 'fix' the cis‐ styrene group in ( Z )‐dimethomorph. The modification of the molecular structure of cinnamamide compounds could be beneficial to improve its practical application performance. Tested the fungicidal activities, it was found that compounds 8j, 9a, 9e, 9i and 9j showed excellent in vivo fungicidal activities (80–100 %) against Pseudoperonospora cubensis at a concentration of 100 mg L −1, while dimethomorph and flumorph were noneffective. Moreover, parts of synthesized indole‐modified cinnamamide derivatives 8 (8a, 8c, 8d and 8j ) and 9 (9c and 9j ) exhibited the same in vivo fungicidal activities against Phytophthora infestans with dimethomorph or flumorph at a concentration of 50 mg L −1 with 100 % inhibition. The biological assay results indicated that indole‐modified cinnamamide derivatives have promising applications in the prevention and treatment of Phytophthora infestans . Abstract :